Le développement durable en Afrique : un processus sous contraintes Expérience de l’industrie minière malienne - Gisèle Belem (VertigO, 2006)
The concept of sustainable development appears due to the environmental movement but also in the continued debate on development concept, as a claim for another globalisation based on alternative development shemes. As such, it can be seen as not suite to african countries under structural adjustement programs since 25 years. In fact these programs narrow the margin for these countries for development policies choice. In spite of this, the sustainable development concept has give rise to the emergence of a communication space based on concepts and values like responsibility, precaution and participation, which are used by different citizens groups. This process favor the expression of alternative proposition which could not be eared before. The malian mining industry illustrate this mobilization potential of the concept of sustainable development.